Expressivité du discours de la presse - Dyoniziak, Jolanta (Wydawnictwo Naukowe UAM, 2012)
The present paper attempts to give an otline of the expressiveness of the discourse encountered in the mass media. Examples are drawn from selected Polish and French periodicals retrieved from the Internet: le Monde, Libération, Tribune, Newsweek, Gazeta Wyborcza. The political stance of these titles is characterized alongside. Main focus is laid on headlines which on account of their localization usually abound most with conspicuous discursive effects, including the ones having specifically expressive character. A priviledged position of the mass media in approaching real life problems is discussed first. Then, various wording techniques implemented in press titles are subject to a thorough analysis. Expressiveness and establishing a particular ranking of values are viewed as two concurrent and close-knit phenomena. Furthermore, expressiveness is shown to reflect current political trends and to comply with main characters of political regime in a given community. Finally, examples exhibiting a high degree of expressive markedness are analyzed. Their peculiar linguistic features result, among others, from delexicalization, NPs exhibiting a strong axiological bias, and neologisms.
The expressiveness of the press discourse
Keywords: expressiveness; headlines; political discourse; press discourse